2012
DOI: 10.1016/j.chroma.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Using chiral liquid chromatography quadrupole time-of-flight mass spectrometry for the analysis of pharmaceuticals and illicit drugs in surface and wastewater at the enantiomeric level

Abstract: This paper presents and compares for the first time two chiral LC-QTOF-MS methodologies (utilising CBH and Chirobiotic V columns with cellobiohydrolase and vancomycin as chiral selectors) for the quantification of amphetamine, methamphetamine, MDA (methylenedioxyamphetamine), MDMA (methylenedioxymethamphetamine), propranolol, atenolol, metoprolol, fluoxetine and venlafaxine in river water and sewage effluent. The lowest MDLs (0.3-5.0 ng L(-1) and 1.3-15.1 ng L(-1) for river water and sewage effluent respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 43 publications
(18 reference statements)
3
43
0
4
Order By: Relevance
“…The same authors reported in another study the increasing of EF of VNF and ATE from influent to effluent, indicating the enrichment of the (R)-ATE and the first eluting enantiomer of VNF [30]. VNF, PHO and ATE were detected with differences in EF between effluent and river waters in United Kingdom [31]. Most of the reported methods were developed to quantify only one therapeutic class; MacLeod et al (2007) developed a reference study of enantiomeric quantification of multiclass pharmaceuticals in the environment, including some beta-blockers (ATE, MET, nadolol, pindolol, PHO, and sotalol), two selective serotonin reuptake inhibitors (citalopram and FLX) and one beta 2 -adrenergic agonist (salbutamol (SBT)), with EF variation for most of the target pharmaceuticals between the influent and the effluent of WWTP [28].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The same authors reported in another study the increasing of EF of VNF and ATE from influent to effluent, indicating the enrichment of the (R)-ATE and the first eluting enantiomer of VNF [30]. VNF, PHO and ATE were detected with differences in EF between effluent and river waters in United Kingdom [31]. Most of the reported methods were developed to quantify only one therapeutic class; MacLeod et al (2007) developed a reference study of enantiomeric quantification of multiclass pharmaceuticals in the environment, including some beta-blockers (ATE, MET, nadolol, pindolol, PHO, and sotalol), two selective serotonin reuptake inhibitors (citalopram and FLX) and one beta 2 -adrenergic agonist (salbutamol (SBT)), with EF variation for most of the target pharmaceuticals between the influent and the effluent of WWTP [28].…”
Section: Introductionmentioning
confidence: 90%
“…Some classes of CP, such as proton pump inhibitors [15,16], antifungals [17], Non Steroid Anti-Inflammatory Drugs (NSAID) [18][19][20][21], beta-blockers [10,12,[22][23][24][25][26][27][28][29][30][31] as well as antidepressants and their metabolites [11][12][13][28][29][30][31][32][33][34], have been reported in environmental matrices, concerning its enantiomers. Regarding antidepressants, enantioselective biodegradation of venlafaxine (VNF) was found in a French river, with racemic VNF at the output of the main WWTP discharging into the river and with EF variation along the river stretch [11].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between CBH and Chirobiotic V columns was performed by Bagnall et al 2012 [23]. Due to the utilisation of a combination of ion exchange, hydrogen bonding and hydrophobic interactions, CBH column was more selective in providing better enantiomeric resolution (i.e.…”
Section: Chirobiotic V and Tmentioning
confidence: 99%
“…62,66,70 Após 2006, a Cromatografia Líquida acoplada à Espectrometria de Massa (LC-MS/MS) começou a destacar-se, passando a ser a técnica de eleição nos trabalhos da área ambiental. 28,54,63,64,68,69,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Apesar de não serem tão usados, os detetores UV e de fluorescência têm sido descritos em alguns trabalhos, 48,82,90,91 como por exemplo em estudos de biodegradação enantiosseletiva desenvolvidos em laboratório, porque as amostras tendem a ser mais limpas e mais concentradas do que as amostras reais de solos, efluentes e águas superficiais. 50,51 Os métodos analíticos modernos para determinação da FE baseiam-se na formação de complexos diastereoisoméricos transitórios com os dois enantiômeros, que podem ser separados por cromatografia, devido às suas diferentes propriedades termodinâmicas.…”
Section: Seletores Quirais Para Cromatografiaunclassified